The Actin Gene Family: Function Follows Isoform - Perrin, Benjamin J (John Wiley & Sons, Inc., 2010)
Although actin is often thought of as a single protein, in mammals it actually consists of six different isoforms encoded by separate genes. Each isoform is remarkably similar to every other isoform, with only slight variations in amino acid sequence. Nevertheless, recent work indicates that actin isoforms carry out unique cellular functions. Here, we review evidence drawn from localization studies, mouse models, and biochemical characterization to suggest a model for how in vivo mixing of actin isoforms may influence cytoskeletal function in cells. © 2010 Wiley-Liss, Inc.